Online contact theory : moderated effects of dual-identity cognitive representation on intergroup attitudes - Lau, Crystal Xin Yi (2018)
Although dual-identity salience has constantly been associated with numerous cross-group benefits, most research has traditionally been done on group differences based on race and religion. More investigation is needed to understand the impact of dual-identity with regards to other, less well-studied social identities. This study investigates the effects of dual-identity cognitive representation on intergroup attitudes in Singapore. Two target out-groups – homosexual people and immigrants in Singapore – were chosen as they are considered to be minority and marginalised groups in the country due to various reasons. According to past literature, interactions between members from different social groups have been shown to lead to optimal intergroup outcomes and improved relations, when the members of those groups hold a dual-identity cognitive representation. Quantity and quality of the intergroup contact, and degree of identification with the subgroup were also studied as potential moderators. In contrast to past research, some of the dual-identity cognitive representations tested in this study predicted more negative attitudes towards the out-group. Results also indicate that quality of past online intergroup contact and subgroup identification predicted attitudes towards homosexuals and immigrants. Specifically, higher quality of past online contact predicted better attitudes towards out-groups. Increased subgroup identification predicted less negative intergroup attitudes for homosexuals and immigrants but predicted more negative attitudes towards the out-group for Singapore citizens. Quantity of past online intergroup contact was not predictive of intergroup attitudes. General implications of the findings as well as future research directions are discussed.